Experimental evaluation of a CPT-based 4-leg active power compensator For distributed generation - Burgos-Mellado, Claudio; Hernández-Carimán, Carlos; Cardenas, Roberto; Saez, Doris; Sumner, M.; Costabeber, Alessando; Morales, Helmo (IEEE, 2017)
Four-wire microgrids (MGs) and distribution systems are inherently unbalanced with the presence of negative and zero sequence components in voltages and currents. In small autonomous systems, the imbalance, in addition to the harmonic distortion produced by nonlinear loads, can significantly affect the power quality, loadability, and stability of the system. Furthermore, in isolated networks with significant generation from intermittent renewable energy sources, the stiffness of the system is reduced and this could amplify the effects of imbalance on the stability and power quality. To mitigate some of these problems, a novel methodology based on the application of a four-leg active power filter is proposed in this paper. The control of the compensator is based on the conservative power theory augmented by resonant controllers. The behavior of the proposed system is demonstrated using an experimental prototype deployed in a laboratory scale MG.